Toxicité de l’huile d’olive extravierge thermo-oxydée chez les Lapins - BELHOUCHAT Nassima; GOUASMIA Afef (My University, 2018)
The effect of consuming thermo-oxidized extra virgin olive oil on rabbits was studied. The animals were divided according to their body weight into 4 groups of 6 rabbits each and which were fed ad libitum for 4 weeks with the incorporation of 15% (W/W) extravirgin olive oil either fresh or heated for 30 min, 60 min and 120 min. The body weight was measured, the urine was analyzed and the blood was collected after sacrifice to examine the level of TOTAL CHOLESTEROL, LDL, HDL and GLYCEMIA. The diet of thermo-oxidized extra virgin olive oil by heating for 60 and 120 min resulted in a decrease in the body weight of rabbits compared to those fed unheated extra virgin olive oil and olive oil heated for 30 min (P < 0.01). This same diet also led to a significant increase (P < 0.01) in total cholesterol, LDL and blood sugar levels. Significantly lower plasma HDL levels (P < 0.01) were observed in rabbits fed a diet that contained extra virgin olive oil heated for 60 and 120 min compared to the control group. The results also showed the appearance of ketone bodies in the urine of rabbits treated with extra virgin olive oil heated for 60 and 120 min. The consumption of thermo-oxidized extra-virgin olive oil is more dangerous for your health than the consumption of fresh olive oil or olive oil with low oxidation value ------------------------------------------------------------------------------------------------- تمت دراسة تأثير استهلاك زيت الزيتون البكر الممتاز المؤكسد حراريا على الأرانب. تم تقسيم الحيوانات حسب وزن الجسم إلى 4 مجموعات تضم كل منها 6 أرانب وتم تغذيتها بالشهرة لمدة 4 أسابيع مع إضافة 15% زيت زيتون بكر ممتاز إما طازجًا أو مسخنًا لمدة 30 دقيقة، 60 دقيقة و تم قياس وزن الجسم لمدة 120 دقيقة، وتحليل البول، وجمع الدم بعد التضحية لفحص مستوى الكوليسترول الكلي، LDL، HDL ونسبة السكر في الدم. أدى النظام الغذائي لزيت الزيتون البكر الممتاز المؤكسد بالحرارة عن طريق التسخين لمدة 60 و 120 دقيقة إلى انخفاض في وزن جسم الأرانب مقارنة بتلك التي تم تغذيتها بزيت الزيتون البكر الممتاز غير المسخن وزيت الزيتون الذي تم تسخينه لمدة 30 دقيقة (P <0.01). أدى هذا النظام الغذائي نفسه أيضًا إلى زيادة كبيرة (P <0.01) في إجمالي مستويات الكوليسترول والبروتين الدهني منخفض الكثافة (LDL) والسكر في الدم. وقد لوحظ انخفاض ملحوظ في مستويات HDL في البلازما (P <0.01) في الأرانب التي تم تغذيتها بنظام غذائي يحتوي على زيت الزيتون البكر الممتاز المسخن لمدة 60 و120 دقيقة مقارنة بالمجموعة الضابطة. كما أظهرت النتائج ظهور أجسام كيتونية في بول الأرانب المعاملة بزيت الزيتون البكر الممتاز المسخن لمدة 60 و 120 دقيقة. يعد استهلاك زيت الزيتون البكر المؤكسد حراريًا أكثر خطورة على صحتك من استهلاك زيت الزيتون الطازج أو زيت الزيتون ذي قيمة الأكسدة المنخفضة. --------------------------------------------------------------------------------------------------- L’effet de la consommation d’une huile d’olive extra vierge thermo-oxydée sur des lapins a été étudié. Les animaux ont été répartis selon leur poids corporel en 4 groupes de 6 lapins chacun et qui ont été nourris ad libitum pendant 4 semaine avec l’incorporationde15%(P/P)d’huiled’oliveextraviergesoitfraîcheouchaufféesdurant30min,60minet120min.Lepoids corporel a été mesuré, les urines ont été analysées et le sang a été récupéré après sacrifice pour examiner le taux de CHOLESTEROL TOTAL, LDL, HDL etGLYCEMIE. Le régime d'huile d’olive extra vierge thermo-oxydée par un chauffage pendant 60 et 120 min a entraîné une diminution du poidscorporeldeslapinscomparativementàceuxnourrisavecunehuiled’oliveextraviergenonchaufféeetunehuiled’olive chauffée pendant 30 min (P < 0,01). Ce même régime a également entrainé une augmentation significative (P < 0,01) du taux de cholestérol total, de LDL et de glycémie. Des niveaux plasmatique significativement baisse du taux de HDL (P < 0.01) ont été observé chez les lapins nourris avec un régime alimentaire qui contient une huile d’olive extra vierge chauffée pendant 60 et 120 min par rapport au groupe témoin. Les résultats ont montré aussi l’apparition des corps cétoniques au niveau des urines des lapins traités par une huile d’olive extra vierge chauffée pendant 60 et 120min. Laconsommationdel'huiled’oliveextraviergethermo-oxydéeestplusdangereusepourlasantéquelaconsommationd'huile d’olive fraîche ou à faible valeurd’oxydation.